Gas Chromatographic Determination and Method Validation of Stigmasterol, Β-Sitosterol, Campesterol and Brassicasterol Contents of Turkish Cottonseed Oil Samples - Cemile Özdemir Yücel; Hasan Ertaş; Fatma Nil Ertas (Turkish Journal of Agriculture: Food Science and Technology)
Plant sterols are important agricultural products for human health and consequently, for nutrition industries. In the present study, free sterol contents of crude Turkish cottonseed oil samples have been determined in a single analytical run by using a solid phase extraction step prior to the detection with a gas chromatography coupled with a flame ionization detector. Free hydroxyl groups of Stigmasterol, β-Sitosterol, Campesterol and Brassicasterol were derivatized by using N-methyl-N-trimethylsilyl trifluoroacetamide to enhance their volatility and, sterol content of the samples were, then, separated from their matrix by using a octadecylsilane cartridge. The eluates were injected into the gas chromatographic system and satisfactory recovery ratios were obtained. After having validated the method, it was applied into the analysis for cottonseed oil samples for their free sterol levels.